1983
DOI: 10.1115/1.3245589
|View full text |Cite
|
Sign up to set email alerts
|

Critical Flashing Flows in Nozzles With Subcooled Inlet Conditions

Abstract: Examination of a large number of experiments dealing with flashing flows in converging and converging-diverging nozzles reveals that knowledge of the flashing inception point is the key to the prediction of critical flow rates. An extension of the static flashing inception correlation of Jones [16] and Alamgir and Lienhard [17] to flowing systems has allowed the determination of the location of flashing inception in nozzle flows with subcooled inlet conditions. It is shown that in all the experiments examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
9

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 0 publications
1
24
0
9
Order By: Relevance
“…Owing to the effect of the metastable state phenomenon, it has been generally found that models based on assumptions of homogeneous equilibrium under-predict the critical discharge rate. Among the models [10,12,13] which calculate the flashing critical mass flux in nozzles, N. Abuaf's [13] model gives the satisfied accuracy. In this model, the pressure undershoot at the flashing inception location can be calculated by the following equation…”
Section: Choking Mass Flow Ratementioning
confidence: 99%
See 4 more Smart Citations
“…Owing to the effect of the metastable state phenomenon, it has been generally found that models based on assumptions of homogeneous equilibrium under-predict the critical discharge rate. Among the models [10,12,13] which calculate the flashing critical mass flux in nozzles, N. Abuaf's [13] model gives the satisfied accuracy. In this model, the pressure undershoot at the flashing inception location can be calculated by the following equation…”
Section: Choking Mass Flow Ratementioning
confidence: 99%
“…Superheated liquid in rapid depressurizing flashing flow has been founds by many investigators [11][12][13][14][15]. Owing to the effect of the metastable state phenomenon, it has been generally found that models based on assumptions of homogeneous equilibrium under-predict the critical discharge rate.…”
Section: Choking Mass Flow Ratementioning
confidence: 99%
See 3 more Smart Citations